Extracellular Vesicles Isolation from Large Volume Samples Using a Polydimethylsiloxane-Free Microfluidic Device - Bajo-Santos, Cristina; Priedols, Miks; Kaukis, Pauls; Paidere, Gunita; Gerulis-Bergmanis, Romualds; Mozolevskis, Gatis; Abols, Arturs; Rimsa, Roberts (MDPI, 2023)
Extracellular vesicles (EV) have many attributes important for biomedicine; however, current EV isolation methods require long multi-step protocols that generally involve bulky equipment that cannot be easily translated to clinics. Our aim was to design a new cyclic olefin copolymer–off-stoichiometry thiol-ene (COC–OSTE) asymmetric flow field fractionation microfluidic device that could isolate EV from high-volume samples in a simple and efficient manner. We tested the device with large volumes of urine and conditioned cell media samples, and compared it with the two most commonly used EV isolation methods. Our device was able to separate particles by size and buoyancy, and the attained size distribution was significantly smaller than other methods. This would allow for targeting EV size fractions of interest in the future. However, the results were sample dependent, with some samples showing significant improvement over the current EV separation methods. We present a novel design for a COC–OSTE microfluidic device, based on bifurcating asymmetric flow field-flow fractionation (A4F) technology, which is able to isolate EV from large volume samples in a simple, continuous-flow manner. Its potential to be mass-manufactured increases the chances of implementing EV isolation in a clinical or industry-friendly setting, which requires high repeatability and throughput. © 2023 by the authors. --//-- Bajo-Santos C., Priedols M., Kaukis P., Paidere G., Gerulis-Bergmanis R., Mozolevskis G., Abols A., Rimsa R.; Extracellular Vesicles Isolation from Large Volume Samples Using a Polydimethylsiloxane-Free Microfluidic Device; (2023) International Journal of Molecular Sciences, 24 (9), art. no. 7971; DOI: 10.3390/ijms24097971; https://www.scopus.com/inward/record.uri?eid=2-s2.0-85159260199&doi=10.3390%2fijms24097971&partnerID=40&md5=34812c9d9de5d8bcd723587a83f1e0d1 published under the CC BY 4.0 licence.
We thank all the donors who participated in this study, the staff of the Latvian Genome Database for providing the samples, and Juris Jansons for taking TEM pictures. The Institute of Solid-State Physics, University of Latvia as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; A4F; extracellular vesicles; microfluidic devices; OSTE–COC; PDMS-free; separation; urine